Hubungan Antara Religiusitas Dengan Tingkat Keharmonisan Keluarga Pada Pasangan Suami Istri - Soraya, Eva; , Dra. Partini, M.Si (2015)
Harmony is the desire of each family, while based on the data obtained is still a lot going on divorce because of family disharmony. Problems in family harmony is the contribution of many factors, one of which is the religiosity of married couples. The purpose of this study is to determine the relationship between religiosity and degree of family harmony and to know the effective contribution of religiosity to the harmony of the family. The hypothesis of this research that there is a positive relationship between religiosity and family harmony. The subjects were residents of RW 04 and RW 07 Village Earth, Laweyan, Surakarta which amounts to 122 people. The sampling technique in this research is purposive sampling. Measuring tool used is the scale of religiosity and family harmony scale. Methods of data analysis done using product moment correlation technique. Based on the analysis of data, it is known the existence of a significant positive relationship between religiosity and family harmony, indicated by value (r) = 0.686; and p = 0.00; (P <0.01), based on the value obtained religiosity variables having the empirical mean (RE) of 91.86 and the mean hypothetical (RH) of 67.5, which means a relatively high religiosity on the subject. Variables known to the average family harmony empirical (RE) of 111.65 and the average hypothetical (RH) is 85, which means family harmony on the subject is high. Effective contribution given to the harmony of family religiosity variable by 47.1%, indicated by the coefficient of determination (r²) = 0.471. The conclusion of this study is There is a significant positive relationship between religiosity and family harmony. This means that the higher the (strong) religiosity, the higher the level of family harmony and effective contribution or the role of religiosity towards family harmony by 47.1%, which is shown by the determinant coefficient (r2) of 0.471 means there are still other factors that 52.9% affect family harmony outside variables religiosity